p Pengaruh Penggunaan Media Scrapbook terhadap Pemahaman Konsep Sistem Sel pada Siswa MA Qur’an Harsallakum: Pengaruh Penggunaan Media Scrapbook terhadap Pemahaman Konsep Sistem Sel pada Siswa MA Qur’an Harsallakum - Meirita Sari; Tri Lestari Budi Asih; Elvida Sari Yunilarosi; Destian Destian; Eka Kurnia Aprillia; Marta Marulina Putri (Al-Alam: Islamic Science Education Journal, 2026)
This study aimed to analyze the effect of using scrapbook media on students’ conceptual understanding of the cell system at MA Qur’an Harsallakum. The research employed a quantitative approach with a one-group pretest–posttest design. The participants consisted of 18 students from class X A. The instrument used was a multiple-choice test oriented toward conceptual understanding (C2–C4), which had been validated for content by three experts and tested for reliability using Cronbach’s Alpha. Data analysis included the Shapiro–Wilk normality test, paired t-test, effect size calculation using Cohen’s d, and normalized gain (N-gain). The results showed an increase in the mean score from 28.33 in the pretest to 29.44 in the posttest. The paired t-test yielded a p value < 0.05, indicating a significant difference before and after the use of scrapbook media. However, the N-gain value of 0.006 and Cohen’s d = 0.08 indicated that the improvement was classified as low with a small effect size. Scrapbook media supports concept visualization, but more optimal instructional time is required.